(untitled) (Acta Scientiarum. Health Sciences, 2015)
Anabolic androgenic-steroids (AAS) include a broad class of synthetic derivatives of testosterone, being nandrolone decanoate the most widely used in sports environment. The aim of this study was to evaluate the metabolic effects of nandrolone decanoate in sedentary and trained adult male rats. We established four experimental groups: sedentary control, sedentary treated, trained control and trained treated. The training had consisted of running on a treadmill for nine weeks. Treated animals received intramuscular injections of nandrolone decanoate (0.5 mg kg-1) during the last four weeks of physical training. The training time as the drug used were not sufficient to significantly reduce body weight gain, but caused a significative decrease on diameter of adipocytes and in the amount of adipose tissue stored, as well as decreased the plasma levels of glucose and total cholesterol.